Urban logistik med gods av varierande storlek - Gedda, Markus; Olsson, Sebastian; Järnberg, Felix; Samuelsson, Marcus; Kjeller, Alfred; Zinga, Arsenije (My University, 2020)
Society is undergoing a change where urbanisation and digitalization are growing like never before. This leads to more crowded cities while e-commerce has become larger than ever. The increasing degree of digitalization and e-commerce have subsequently led to the emergence of new customer needs. Customers demand fast and cheap deliveries as well as stricter requirements are introduced on these being environmentally sustainable. This, in combination with the enormous ow of goods of di erentiated sizes, present companies with new and tough challenges. The purpose of this study is to investigate how goods with varying sizes, e ciently and sustainably can be distributed i Swedish urban areas. The study is based on a literature review and ve interviews from four di erent companies in retailing, transportation and housing development. The literature review, in the eld of urban logistics, made it possible to construct a theoretical framework. The conducted interviews provided an insight into how these companies work with transportation today, as well as their opinions on alternative methods and future possibilities. The data gathered from these interviews constituted the empirical framework. By relating the collected empirical data to existing theories, three main conclusions could be concluded from analysing the di erent delivery methods. The study showed that the use of housing integrated parcel lockers was considered the best delivery method for smaller parcels. It is important to note is that an investment in infrastructure is necessary since an established network does not exist in Sweden today. Further results from the study presented is that home delivery, in combination with smart locks was the best solution for larger packages. The use of urban consolidation centres also proved to be bene cial for consolidating goods outside urban areas. This enables transports to be conducted with vehicles of appropriate sizes and high ll rates to parcel lockers as well as home deliveries. Note: The report is written in Swedish
Keywords: Urban logistics; last mile deliveries; sustainable logistics; home deliveries; parcel lockers; pick up points and urban consolidation centres (UCC)